The Effects of Information And Communication Technology In Hungarian Economic Sectors - Peter Sasvari (International Journal of Computer Science & Engineering Technology (IJCSET), 2011)
As the author could not find a reassuring mathematical and statistical method in the literature for studying the effect of information communication technology on enterprises, the author suggested a new research and analysis method that he also used to study the Hungarian economic sectors. After a brief introduction to the theoretical background of the Information Age, the author examines the question of what factors have an effect on their net income is essential for enterprises. First, the potential indicators related to economic sectors were studied, then the author compared those indicators to the net income of the surveyed enterprises. The data resulting from the comparison showed that the growing penetration of electronic marketplaces contributed to the change of the net income of enterprises in various economic sectors. Among all the potential indicators, only the indicator of electronic marketplaces has a direct influence on the net income of enterprises. It was practical to determine two clusters based on the potential indicators.
Keywords: M13; M15; 330; Information society; ICT; Economic sector; Electronic presence; Electronic marketplace